Sejarah Gereja Belanda Austin Friars di City of London: Refleksi Sejarah Gerakan Reformasi — Harapan dan Tantangan - Henk ten Napel (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2017)
Abstract In the centre of the City of London one can find the Dutch Church Austin Friars. Thanks to the Charter granted in 1550 by King Edward VI, the Dutch refugees were allowed to start their services in the church of the old monastery of the Augustine Friars. What makes the history of the Dutch Church in London so special is the fact that the church can lay claim to being the oldest institutionalised Dutch protestant church in the world. As such it was a source of inspiration for the protestant church in the Netherlands in its formative years during the sixteenth century. Despite its long history, the Dutch Church is still alive and well today. This article will look at the origin of this church and the challenges it faced and the developments it experienced during the 466 years of its existence. Abstrak Di pusat distrik keuangan di London (City of London) terdapat sebuah gereja dengan nama Gereja Belanda Austin Friars. Berkat surat keputusan yang dikeluarkan Raja Edward VI pada tahun 1550, pengungsi-pengungsi Belanda diberi hak untuk mengadakan kebaktian bersama di dalam gereja biara frater-frater Agustin. Sejarah Gereja Belanda di London menarik sekali, karena gereja ini dapat dikatakan adalah gereja kelembagaan yang bersifat protestan dan berbahasa Belanda yang pertama di dunia. Dalam situasi ini gereja ini menjadi sumber ilham buat Gereja Protestan di Nederland yang sedang berkembang pada abad ke-16. Walaupun sudah berumur lanjut, namun Gereja Belanda masih tetap hidup dan sehat sampai hari ini. Artikel ini dimaksudkan untuk melihat sejarah gereja tersebut sejak permulaannya serta tantangan dan perkembangan yang dialami dalam sejarahnya selama 466 tahun lebih.